Scientific and methodological approaches to the evaluation of innovation development strategy of post offices - Krupska, Viktoriya (Видавництво Львівської політехніки, 2013)
The report identifies the main scientific and methodological approaches to evaluation of performance of innovative development strategy of mail service enterprises.
Keywords: innovative development; strategy; mail service; approaches